Robotics: future of schooling in Bangladesh - Noor, Abtahi; Rahman, Tasmia; Ahmed, Monjur; Eshika, Opshora Noshin; Fardin, Faraz; Labby, Ahshanul Mahbub (Brac University Research For Development Club (BURED), 2024)
Cataloged from PDF version of the article.